1983
DOI: 10.1038/jcbfm.1983.34
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Glucose Metabolism as a Function of Age in Man: Influence of the Rate Constants in the Fluorodeoxyglucose Method

Abstract: Summary: Measurement of the local cerebral metabolic rate of glucose (LCMRGlc) with the fluorodeoxyglucose (FDG) method requires the utilization of appropriate val ues for the rate constants of the transport and phosphor ylation processes, We measured these rate constants as a function of age to determine whether a decline in LCMRGlc as a function of age, in prior studies with the The deoxyglucose method originally developed by Sokoloff et aL (1977) and applied to humans by Reivich et aL (1979), Phelps et aL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…In our in vitro metabolic studies, we chose controls matched for both chronological age and number of intervening hours before autopsy so that any possible age‐related decline would be eliminated. PET studies have consistently reported the lack of an age‐related effect on glucose utilization among normal subjects 29–32 …”
Section: Discussionmentioning
confidence: 99%
“…In our in vitro metabolic studies, we chose controls matched for both chronological age and number of intervening hours before autopsy so that any possible age‐related decline would be eliminated. PET studies have consistently reported the lack of an age‐related effect on glucose utilization among normal subjects 29–32 …”
Section: Discussionmentioning
confidence: 99%
“…Even the studies that do not correct at all are conflicting. For example de Leon et al, 1987; Hawkins et al, 1983; Kuhl et al, 1982 found no changes with age while Herholz et al, 2002; Loessner et al, 1995; Moeller et al, 1996; Petit-Taboue et al, 1998; Yoshizawa et al, 2014 found change with age. The studies that did not find a change were performed when PET scanner resolutions were very poor which may account for the lack of results.…”
Section: Introductionmentioning
confidence: 97%
“…First, the difference in age between the patient and the control subjects is unlikely to explain the results. The slight decrease of frontal glucose metabolism with ageing remains questionable [39], and has only been reported in elderly subjects [40]. Moreover, the whole cortex mean value in the control subjects studied here was 5.86 ± l.OOmg/lOOml/minwhichis not significantly different from that (6.41 ± 1.30) reported in a different group of slightly older normal controls previously studied with the same tomograph [41], Moreover, this val ue is consistent with that reported for the whole cortex in slightly younger normal sub jects by different authors [for instance, 5.19 ± 0.90 mg/100 ml/min reported by Gur et al"…”
mentioning
confidence: 99%